PENINGKATAN KETERAMPILAN MENULIS TEKS CERITA INSPIRATIF MELALUI STRATEGI PEMODELAN - Endang Kartika Utami (Ideguru: Jurnal Karya Ilmiah Guru, 2020)
The purpose of this research is to improve writing skill of students grade nine at SMPN 2 Sewon through modelling strategy to the naterial of writing inspirative story text. To solve the problem, the writer does class action research(PTK )through modelling strategy. It is used to make easy the teacher in doing the teaching of writing and to make the students in writing inspirative story text.The procedurs of the research are planning, doing action, observation, and reflection the result of avtion. The time in doing this research is started from January up to April 2019. Technique of collection data uses qualitative and qualitative descriptive. While the result of studentswriting testis analysedby comparative descriptive system between the first data and action result between cycle. Based on the analysing data and reflection of learning process, it is gained the last result whichis significant to the result of the research by implementing through modelling strategy, it can improve writing skill of students inspirative story text the avarege of cycle I is 72,41% and cycle 2 is 89,66%. Based on result, it can beconcluded, the using of modelling can improve writing skill of students inspirative story text.